Cytotoxic lanostanes from fruits of Garcinia wallichii Choisy (Guttiferae) - Sakchai Hongthong (2018)
© 2016 Elsevier Ltd Five new lanostanes, wallichinanes A–E (1–5) together with a known lanostane derivative 6 were isolated from the cytotoxic hexanes extract of fruits of Garcinia wallichii Choisy (Guttiferae). The structures of the isolated compounds were established by analysis of spectroscopic data, X-ray diffraction technique as well as comparison with the literature data. The cytotoxicity of all isolated compounds against a panel of cultured cancer cell lines was evaluated. Compound 4 exhibited good cytotoxicity with ED50values ranging from 3.91 to 7.63 μM.